(untitled) (Global Journal of Human-Social Science, 2012)
Chongming Island Is under the framework of Shanghai administration. It is an alluvial Island in the mouth ol the Yangtze River. The area is 1041 km2 and the population is about 700,000 inhabitance. An expected tunnel will combine the island to the main land in the future. The local population will increase and the island is becoming very attractive to tourists. The island could be regarded as a Peri Urban system of Shanghai neighborhood. All these turn Chongming Island into an ecological conservation project directed by Shanghai Academy Agricultural Science (SAAS) organization. The following are few ideas that can reduce the hazard of soil, water, air contamination and other environmental distur-bances. Also activities proposed to change the island agricultural features, ecological education campaign and eco-agro tourism projects.